DYNAMICS OF SIgA CONTENT IN BREAST MILK WHEN RISK FACTORS AND LACTATIONAL CHARACTERISTICS ARE CONSIDERED - Nataliya Gromnatska (Acta Medica Leopoliensia)
The leading role associated with an anti-infective action of breast milk belongs to secretory IgA (SIgA). Therefore, the determination of the level of SIgA in colostrum and milk of mothers with different lactation levels and mothers at risk at different levels and duration of lactation has a practical interest.